2015
DOI: 10.1136/heartjnl-2015-307691
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction and influenza: a meta-analysis of case–control studies

Abstract: ObjectiveAcute myocardial infarction (AMI) is the leading cause of death and disability globally. There is increasing evidence from observational studies that influenza infection is associated with AMI. In patients with known coronary disease, influenza vaccination is associated with a lower risk of cardiovascular events. However, the effect of influenza vaccination on incident AMI across the entire population is less well established.MethodThe purpose of our systematic review of case–control studies is twofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
210
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 267 publications
(224 citation statements)
references
References 37 publications
4
210
0
10
Order By: Relevance
“…A number of studies show that influenza is associated with AMI [4][5][6][7]. In a meta-analysis of available case-control studies, we showed that influenza infection doubles the risk of AMI [4].…”
Section: Influenza and Amimentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies show that influenza is associated with AMI [4][5][6][7]. In a meta-analysis of available case-control studies, we showed that influenza infection doubles the risk of AMI [4].…”
Section: Influenza and Amimentioning
confidence: 99%
“…There is, in fact a large body of evidence from both randomized controlled clinical trial (RCT) and observational studies which suggest that influenza vaccine protects against AMI [4]. We were the first to calculate vaccine effectiveness against AMI and found that influenza vaccine effectiveness was 45% against AMI [5].…”
Section: Cvd and Influenza Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…8 and the highest risk is among those with established CVD. 9 The mechanism by which influenza increases the risk of CV events is unclear, but may be related to triggering of rupture of vulnerable atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%